Simulation of fluid-structure interaction during the phaco-emulsification stage of cataract surgery. (15th January 2022) - Wang, Zhaokun; Wang, Chenglei; Zhao, Fuwang; Qi, Nan; Lockington, David; Ramaesh, Kanna; Stewart, Peter S.; Luo, Xiaoyu; Tang, Hui
Highlights: A dedicated FSI model for cataract surgery is developed for the first time. Complex fluid-iris interaction including severe structural nonlinearity is addressed. The physical mechanism of IFIS is explored from the FSI perspective. This study provides clinicians with some guidelines to improve surgical protocol. Abstract: During cataract surgery the clouded lens is broken up by phacoemulsification. The iris can become highly mobile and could be entrained by the phacoemulsification probe, under a condition known as intraoperative floppy iris syndrome (IFIS). In this study we explore the mechanism of IFIS during phacoemulsification-based cataract surgery using fluid-structure interaction (FSI) simulations. As the first study of its kind, we developed a simplified two-dimensional simulation framework and utilized it to elucidate the dynamics of the iris and surrounding aqueous humor during phaco-emulsification. Three types of iris dynamics were observed when the phaco probe was operated in the torsional vibration mode and placed at various locations in the anterior chamber, which we termed as the repulsion (where the iris is repelled by the probe), attraction (where the iris is drawn toward the probe) and adhesion mode (where the iris is adhered to the probe at some point along its length), respectively. The anterior chamber is partitioned into different zones which exhibit each of these three modes. Furthermore, the effects of iris stiffness and length as well as the power and frequency of the probe operation were investigated. It was found that IFIS could be mitigated by increasing the iris stiffness, shortening the iris length (i.e., pupil dilation), decreasing the power of the emulsification probe, and maintaining the probe operation frequency in a range around the frequency of the iris' fundamental bending mode. This study provides new physical insights into the dynamics of fluid-iris interaction during phaco-emulsification, which may guide clinicians to optimize their surgical protocol. Graphical abstract: Image, graphical abstract